NIMG-58. IMMUNOPET OF 89ZR-DFO-CD69 AB VISUALIZES T-CELL ACTIVATION AND PREDICTS SURVIVAL FOLLOWING IMMUNOTHERAPY IN MURINE GBM MODEL. (14th November 2022) - Nisnboym, Michal; Vincze, Sarah; Raphael, Itay; Sneiderman, Chaim; Xiong, Zujian; Li, Bo; Day, Kathryn; Latoche, Joseph; Nedrow, Jessie; Anderson, Carolyn; Pearce, Thomas; Pollack, Ian; et al.
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most malignant brain tumor in adults, with a dismal prognosis despite aggressive therapy. Immunotherapy is currently being evaluated as a treatment modality for recurrent GBM. MRI is not adequate for response assessment to immunotherapy even after using refined response assessment criteria. Thus, there is a need for the development of neuroimaging techniques for response assessment. T-cells are key mediators of cancer immunotherapy responses and upregulation of CD69 is a marker of T-cell activation. Our aim is to use PET/CT imaging to non-invasively quantify CD69 in vivo, following immunotherapy, and correlate the expression to survival. METHODS: CD69 was evaluated by flow cytometry and immunofluorescence staining on human and mouse in vitro activated T-cells and on dissociated tumors from GL261 glioma-bearing mice treated with anti-PD1/anti-CTLA4 immunotherapy (ICI). Single-cell RNA sequencing (ScRNAseq) datasets from recurrent GBM patients receiving (n=20) or not receiving (n=22) ICI were examined for CD69 expression on tumor infiltrating lymphocyte (TIL) populations. PET/CT was performed on mice (n=30) receiving radiolabeled anti-CD69 antibody ( 89 Zr-DFO-anti-CD69) to evaluate response to ICI therapy. Standard uptake values (SUV) were compared between ICI and controls and in relationship to survival. RESULTS: We confirmed CD69 upregulation upon T-cell activation in vitro. Ex vivo, CD69 expression significantly increased on TILs early after ICI treatment compared to control (63.46% vs 24.37% CD69+/TILs, respectively; p=0.017). ScRNAseq demonstrated significant elevated CD69 expression in almost all TIL populations tested in recurrent GBM patients treated with ICI compared with a control group. ImmunoPET demonstrated significantly higher anti-CD69 tracer uptake in ICI-treated mice compared with controls. Most importantly, we observed a strong positive correlation between survival and immunoPET SUV (r=0.9425, p=0.016) in the ICI-treatment group, but not within the control group. CONCLUSIONS: Our study demonstrates the potential incorporation of CD69 ImmunoPET as response assessment to ICI for GBM patients.